INNOVATIVE DIGITAL TOOLS FOR ENHANCING ENGLISH LANGUAGE TEACHING (ELT) EFFECTIVENESS - Кадырбаева Н.Ж.; Иманова Г.С. (Publisher of Kostanay Regional University named after Akhmet Baitursynuly, 2025)
This article aims to explore the potential of integrating modern digital tools, such as Virtual Reality (VR), gamification, and AI-driven platforms, to enhance the effectiveness of English Language Teaching (ELT). The study analyzes practical methods for applying these technologies in English lessons to develop students' speaking, listening, and intercultural communication skills.
Keywords: digital tools; English Language Teaching; effectiveness; Virtual Reality; Artificial Intelligence